2010
DOI: 10.1158/1535-7163.mct-10-0637
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin G–Associated Kinase Is Necessary for Osteosarcoma Cell Proliferation and Receptor Trafficking

Abstract: Osteosarcoma is the most frequent primary malignant bone tumor among the children. The advent of neoadjuvant chemotherapy significantly improved the prognosis of patients with osteosarcoma in the 1980s, but it has since plateaued in the past decades. Recently, one of the most researched areas in sarcoma treatment is tyrosine kinases. Here, we describe research on a serine/threonine kinase, cyclin G-associated kinase (GAK), which has not been reported in osteosarcoma previously. In this study, a lentiviral base… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 40 publications
0
44
0
Order By: Relevance
“…GAK is overexpressed in U2OS osteosarcoma cells, which lack EGFR expression, and knockdown of GAK inhibits their proliferation [31]. Therefore, we hypothesized that luteolin and/or gefitinib may induce apoptotic cell death of U2OS cells as well as PC-3 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GAK is overexpressed in U2OS osteosarcoma cells, which lack EGFR expression, and knockdown of GAK inhibits their proliferation [31]. Therefore, we hypothesized that luteolin and/or gefitinib may induce apoptotic cell death of U2OS cells as well as PC-3 cells.…”
Section: Resultsmentioning
confidence: 99%
“…GAK is also overexpressed in KHOS and U2OS osteosarcoma cells; its overexpression is associated with poor prognosis, and siRNA-mediated knockdown of GAK decreases the proliferation of osteosarcoma cells [31], suggesting that GAK plays a pivotal role in the control of the proliferation rate of osteosarcoma cells. Unlike other osteosarcoma cell lines (HOS, MG-63, and KHOS/NP), U2OS cells lack expression of the EGFR, the well-known target of gefitinib; therefore, GAK is a putative bona fide target of gefitinib in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…4 GAK is overexpressed in U2OS osteosarcoma cells and knockdown of GAK inhibits their proliferation. 10 We recently showed that GAK is modified and overexpressed in metastatic cancer cells, and that nuclear GAK is expressed at high levels in surgical specimens from prostate cancer patients with a positive correlation with the Gleason score. 9 These reports and our results here suggest that GAK functions in the regulation of proper M phase progression, in addition to cytoplasmic membrane trafficking.…”
Section: Discussionmentioning
confidence: 98%
“…9 The GAK level is also augmented in osteosarcoma cells of patients with a poor prognosis, and siRNA-mediated knockdown of GAK decreases the proliferation of osteosarcoma cells. 10 GAK harbors 4 structural domains: an N-terminal Ser/Thr kinase (K) domain, a PTEN-like (T) domain, a clathrin-binding (CB) domain, and a C-terminal J domain. Hampered clathrindependent trafficking caused by GAK knockout in fibroblasts is rescued by expressing the CB and J domains, suggesting that they play pivotal roles in GAK function.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 GAKs' role in vesicle trafficking was described initially, 25 but subsequent studies identified a second role in cytokinesis, 26 and in fact it was this second role that enabled it to be identified in several recent RNAi screens. [27][28][29] On the basis of an siRNA screen, we have extended these characterizations to include a role for GAK in the adaptation of cancer cells to hypoxia and to an effect on cancer cell survival that cannot be suppressed by the activation of NF-κB. Since NF-κB is a potent tumor survival pathway and the object of many cancer therapeutic strategies, 30,31 an inhibitor that can function independently of the NF-κB survival pathway could be an important therapeutic modality.…”
Section: Discussionmentioning
confidence: 99%